Enzyme Inhibition, Antimicrobial Potentials of Saponaria prostrata plant extracts - Aras, Abdülmelik; Alan, Yusuf (My University, 2022)
Saponaria prostrata is a medicinal plant that contains various secondary metabolites such as phenolic acid, flavonoids, triterpenoids, and fatty acids that are related to some biological activities. In this study, we evaluated the enzyme inhibitory, antimicrobial potentials of S. prostrata. The antimicrobial activity of S. prostrata was measured using three Gram-positive, four Gram-negative bacteria species, and three fungi species. The highest antibacterial activity was detected against the Staphylococcus aureus ATCC 25923 (13±0.81 mm inhibition zone). The enzyme inhibition effect (IC50 values) of S. prostrata were calculated against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and ?-glycosidase (?-Gly) as 2.39 mg/mL, 3.69 mg/ml, and 2.48 mg/mL, respectively.